What makes a good person? - SINGH, Ishan (Institutional Knowledge at Singapore Management University, 2020)
A few weeks ago, my editor sent me this New York Times article about “how to be good”, asking if I'd be interested to pen a commentary based on a similar premise. It seemed easy enough at the time, so I readily agreed. But once I got down to actually thinking about the subject, I found myself at a loss for words.